(untitled) - Kruger, T.P.J. (Tjaart)

Investigating the stability and photophysics of organic solar cell active layers based on multicomponent polymer materials (University of Pretoria, 2025)
Thesis (PhD (Physics))--University of Pretoria, 2025.